Spatiotemporal Resolved Leaf Angle Establishment Improves Rice Grain Yield via Controlling Population Density - Wang, Rongna (iScience, 2020)
Leaf angle is mainly determined by the lamina joint (LJ) and contributes to ideal crop architecture for high yield. Here, we dissected five successive stages with distinct cytological features of LJs spanning organogenesis to leaf angle formation and obtained the underlying stage-specific mRNAs and small RNAs, which well explained the cytological dynamics during LJ organogenesis and leaf angle plasticity. Combining the gene coexpression correlation with high-throughput promoter analysis, we identified a set of transcription factors (TFs) determining the stage- and/or cytological structure-specific profiles. The functional studies of these TFs demonstrated that cytological dynamics determined leaf angle and that the knockout rice of these TFs with erect leaves significantly enhanced yield by maintaining the proper tiller number under dense planting. This work revealed the high-resolution mechanisms of how the cytological dynamics of LJ determined leaf erectness and served as a valuable resource to remodel rice architecture for high yield by controlling population density.